2001
DOI: 10.1074/jbc.m100578200
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium falciparum Bifunctional Ornithine Decarboxylase, S-Adenosyl-l-methionine Decarboxylase, Enables a Well Balanced Polyamine Synthesis without Domain-Domain Interaction

Abstract: In the human malaria parasite Plasmodium falciparum (Pf), polyamines are synthesized by a bifunctional enzyme that possesses both ornithine decarboxylase (ODC) and S-adenosyl-L-methionine decarboxylase (AdoMetDC) activities. The mature enzyme consists of the heterotetrameric N-terminal AdoMetDC and the Cterminal dimeric ODC, which results in the formation of a heterotetrameric complex. For the native bifunctional protein a half-life longer than 2 h was determined, which is in contrast to the extreme short half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 43 publications
2
56
0
Order By: Relevance
“…In this study, we demonstrate that T. gondii lacks ODC and ADC activity, and therefore is auxotrophic for polyamines. These results agree with the observed growth requirement of T. gondii for host polyamines reported by others (Moraes et al, 2004;Seabra et al, 2004), but distinguish T. gondii from other members of the apicomplexa that have the ability to synthesize polyamines (Keithly et al, 1997;Wrenger et al, 2001). T. gondii has previously been shown to have a highaffinity putrescine transporter, demonstrating the ability to scavenge host-derived putrescine (Seabra et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, we demonstrate that T. gondii lacks ODC and ADC activity, and therefore is auxotrophic for polyamines. These results agree with the observed growth requirement of T. gondii for host polyamines reported by others (Moraes et al, 2004;Seabra et al, 2004), but distinguish T. gondii from other members of the apicomplexa that have the ability to synthesize polyamines (Keithly et al, 1997;Wrenger et al, 2001). T. gondii has previously been shown to have a highaffinity putrescine transporter, demonstrating the ability to scavenge host-derived putrescine (Seabra et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…The various members of the apicomplexa have different methods for polyamine biosynthesis: E. tenella and P. falciparum have an active ODC (Keithly et al, 1997;Wrenger et al, 2001), whereas C. parvum has an ADC (Keithly et al, 1997); these differences may be the result of different intracellular localizations of these parasites. Most information is available for the malaria parasite P. falciparum, which has been shown to possess a bifunctional ODC-adenosylmethionine decarboxylase that is responsible for polyamine biosynthesis (Wrenger et al, 2001). The activity of the P. falciparum enzyme has been shown to be significantly blocked by putrescine analogues that exhibited 1300-fold higher activity toward the parasite compared with DFMO (Das Gupta et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synonymous codons were chosen to ensure that the positional codon frequency of low/intermediate and high usage codons are similar to the frequency used by that of the E. coli host [17]. Codon-harmonised nucleotides 1-1461 (GeneArt, Regensburg, Germany) encoding the core of PfAdoMetDC (487 residues) [11] [9]), which encodes half of the hinge region (wtPfAdoMetDC-hinge, 660 residues) with an N-terminal Strep-tag. In addition, expression of the full-length PfAdoMetDC/ODC proteins from the pASK-IBA3 constructs containing harmA/wtO and wtA/wtO [8] were also compared.…”
Section: Pfadometdc/odcmentioning
confidence: 99%
“…Both of these decarboxylase activities function independently of each other within the bifunctional complex [9], although it was shown that inter-and intradomain interactions modulate both activities [10]. In contrast to their single-enzyme orthologues in other organisms, the PfODC activity in the bifunctional enzyme is strongly feedback-inhibited by putrescine, whereas PfAdoMetDC activity is not stimulated by putrescine [9,11]. In the absence of known regulatory mechanisms that control polyamine levels in other organisms, the presence of a single PfAdoMetDC/ODC polypeptide has been suggested to allow regulation of polyamine pools in plasmodia [9].…”
Section: Introductionmentioning
confidence: 99%